Associations of socioeconomic position in childhood and young adulthood with cardiometabolic risk factors: the Jerusalem Perinatal Family Follow-Up Study. Issue 1 (14th July 2016) - Savitsky, B; Manor, O; Friedlander, Y; Burger, A; Lawrence, G; Calderon-Margalit, R; Siscovick, D S; Enquobahrie, D A; Williams, M A; Hochner, H
Abstract : Background: Several stages in the life course have been identified as important to the development of cardiovascular disease. This study aimed to assess the associations of childhood and adulthood socioeconomic position (SEP) and social mobility with cardiometabolic risk factors (CMRs) later in life. Methods: We conducted follow-up examinations of 1132 offspring, aged 32, within a population-based cohort of all births in Jerusalem from 1974 to 1976. SEP was indicated by parents' occupation and education, and adulthood SEP was based on offspring's occupation and education recorded at age 32. Linear regression models were used to investigate the associations of SEP and social mobility with CMRs. Results: Childhood-occupational SEP was negatively associated with body mass index (BMI; β=−0.29, p=0.031), fat percentage (fat%; β=−0.58, p=0.005), insulin (β=−0.01, p=0.031), triglycerides (β=−0.02, p=0.024) and low-density lipoprotein cholesterol (LDL-C; β=−1.91, p=0.015), independent of adulthood SEP. Adulthood-occupational SEP was negatively associated with waist-to-hip ratio (WHR; β=−0.01, p=0.002), and positively with high-density lipoprotein cholesterol (HDL-C; β=0.87, p=0.030). Results remained similar after adjustment for smoking and inactivity. Childhood-educational SEP was associated with decreased WHR and LDL-C level (p=0.0002), and adulthood-educational SEP was inversely associated with BMI (p=0.001), waist circumference (p=0.008), WHR (p=0.001) and fat% (p=0.0002) and positively associated with HDL-C (p=0.030). Additionally, social mobility (mainly upward) was shown to have adverse cardiometabolic outcomes. Conclusions: Both childhood and adulthood SEP contribute independently to CMR. The match–mismatch hypothesis may explain the elevated CMRs among participants experiencing social mobility. Identification of life-course SEP-related aspects that translate into social inequality in cardiovascular risk may facilitate efforts for improving health and for reducing disparities in cardiovascular disease.